"Brace Technology" Thematic Series - The Lyon approach to the conservative treatment of scoliosis - de Mauroy, Jean Claude (BioMed Central, 2011)
The Lyon Brace, or adjustable multi-shell brace, has been used for more than 60 years. The use and function of the Lyon Brace includes: - The utilization of one or two corrective plaster casts, which enables a true lengthening of the concave ligaments. - An oriented CAD-CAM moulding in 3D auto correction after the removal of the plaster cast. - A blueprint adapted to Lenke's classification. - A specific physiotherapy program. BACKGROUND: Pierre Stagnara created the Lyon Brace in 1947. The brace has the following characteristics: - It adjusts to allow for a child's growth of up to seven centimetres and for an increase in weight of up to seven kilograms. - It is 'active' in that the rigidity of the PMM (polymetacrylate of methyl) structure stimulates the user to auto-correct. The active axial auto-correction decreases the pressures of the brace on the trunk. - It is decompressive in that the effect of extension between the two pelvic and scapular girdles decreases the pressure on the intervertebral disc allowing for more effective pushes in the other planes. - It is symmetrical making it both more aesthetically pleasing and easier to build. - It is stable at both shoulders and pelvic girdle, facilitating the intermediate 3D corrections. - It is transparent. The pressure of the shells on the skin can be directly controlled so "pads" are usually not necessary. BRACE DESCRIPTION: Two metal bars are fixed vertically, one anterior the other posterior and all shells are attached from the bottom to the top in this order: - Two pelvic shells ensure an optimal stability of the brace. - One lumbar shell T12-L4, which can be either independent or extending, at the abdominal chondrocostal level. - One thoracic shell at the level of the thoracic convexity. - One opposite thoracic shell used as a counter push. - One shoulder balance shell on the side of the thoracic convexity. LONG TERM FOLLOW UP RESULTS: This is a retrospective study of 1,338 completed treatments checked a minimum of two years after weaning from the brace. Only 5% of the curves progressed more than 5° from the initial magnitudes. This translates to an effectiveness index of 0.95. A subset of 174 subjects who started treatment at Risser 0 was isolated. The global progressive angular mean curve was superimposed on the statistic general curve and the effectiveness index was calculated at 0.80. The Surgery rate was just 2% of the patients presenting with an initial curve below 45°. CONCLUSION: The Lyon Brace is the historical reference of bracing AIS. To be fully effective, it requires the patient to wear a plaster cast for at least one month and receive specific physiotherapy training. Although this is a retrospective study, the results are very positive, and clearly indicate a need for a prospective study.